Legal Accountability Towards Children As Perpetrators Of The Criminal Act Of Preplanted Murder In The Indonesian Criminal Justice System - Surahman; Winda Bella Puspita (DE'RECHTSSTAAT, 2025)
The purpose of this research is to find out the factors that cause children to commit the crime of murder and to find out and analyse, the judge's consideration in imposing a verdict on children as perpetrators of the crime of murder in Case No. 3/Pid.Sus-Anak/2022/PN Smr. The method used in this research is normative legal research method. This method includes research on library materials that are studied using a statutory approach and a case approach. The legal materials used include primary, secondary and tertiary legal materials. The results showed that the factors that cause children to commit the crime of murder include internal factors such as the psychiatric, biological, and moral conditions of children, as well as external factors including the socio-cultural environment, economy, and easy access to adult content through mass media. The judge's consideration in deciding case number 3/Pid.Sus-Child/2022/PN Smr by applying article 338 of the Criminal Code on murder was not appropriate, the judge should have applied article 340 of the Criminal Code on premeditated murder in trying and deciding case number 3/Pid.Sus-Child/2022/PN Smr.